Building on Mobile towards Better Stuttering Awareness to Improve Speech Therapy - Madeira, Rui Neves (2013)
This paper describes the project I Aware my Stuttering , which is a system with a focus on a mobile application for smartphones directed to people who stutter. This software will allow users to register their stuttering related situations, registering, for example, the contexts in which they occur, the interlocutors and their reactions to the situations, and the emotions felt. The application provides a reporting module that includes charts to help visualizing how stuttering situations evolve according to several features. It will help promote daily self-monitoring of speech as a means of controlling stuttering, being personalized according to the user profile. The system also offers a module for the speech therapist, which can monitor and receive reports related to users which are her/his patients. This collected data will improve the therapeutic process by enhancing discussion about registers performed immediately after a real context situation. Additionally, this paper presents a first user study conducted to assess and validate the project’s purpose and the central module for registration of stuttering related situations.